Divinity and Power in Minute Particulars: Politics and Panentheism in the Implicit Religion of Marist Socks - Keenan, William (Implicit Religion, 2009)
The intention here is to explore the “implicit spirituality” of socks as a component of the religious wardrobe in relation to the larger theological themes of panentheism, sacramentalism and related mystical orientations. The early nineteenthcentury case of the Marist socks is employed to demonstrate the fecundity and utility of “implicit religion” as a concept and category that helps “make sense” of the Marist Founder’s valorization of this otherwise relatively insignificant item of male dress. In the grander theological and sociological scheme of things, Marist socks assume religious significance as a salutary sartorial symbol. Drawing on the Marist archives, the sock history of the Little Brothers of Mary is uncovered to reveal how, in religion, even the most neglected and least important of things in the eyes of the world can assume extraordinary spiritual and political significance.